Neurite dispersion and density mediates the relationship between cardiorespiratory fitness and cognition in healthy younger adults. (3rd May 2022) - Callow, Daniel D.; Purcell, Jeremy J.; Won, Junyeon; Smith, J. Carson
Abstract: Growing evidence suggests physical activity and cardiorespiratory fitness are associated with better cognition across the lifespan. However, the neurobiological underpinnings relating fitness and cognition remain unclear, particularly in healthy younger adults. Using a well-established and popular multi-compartment diffusion modeling approach, called Neurite Orientation and Dispersion and Density Imaging (NODDI), we investigated the relationship between physical fitness (measured via a 2-min walk test), cognition (fluid and crystallized), and gray and white matter microstructure, in a large sample (n = 816) of healthy younger adults (ages 22–35 years) from the human connectome project (HCP). Concurrent with previous literature, we found that fitness was positively associated with both fluid and crystallized cognition. Furthermore, we found that physical fitness was negatively associated with white matter orientation dispersion index (ODIWM ) around the cerebellar peduncle and was negatively associated with widespread cortical and subcortical gray matter neurite density index (NDIGM ). Lower ODIWM of the cerebral peduncle was associated with better fluid cognitive performance, while lower NDIGM was associated with better crystallized cognition. Finally, we found that while ODIWM partially mediated the relationship between fitness and fluid cognition, NDIGM partially mediated the relationship between fitness and crystallized cognition. This study is the first to explore the relationship between physical fitness and white and gray matter microstructure measures using NODDI. Our findings suggest that in addition to improved cognitive performance, higher physical fitness may be associated with lower white matter tract dispersion and lower neurite density in the cortical and subcortical gray matter of healthy younger adults. Highlights: Two minute walk distance is associated with better fluid and crystallized cognition in healthy younger adults. Walk distance is associated with lower white matter neurite dispersion and lower gray matter neurite density. White matter neurite dispersionand gray matter density were associated with better fluid and crystallized cognition. White matter neurite dispersion partially mediates relationship between 2 min walk distance and fluid cognition. Gray matter neurite density partially mediates relationship between walk distance and crystallized cognition.